Magnetospheric response to geomagnetic storms - Booth, Timothy Charles (University of Leicester, 2018)
Geomagnetic storms are well observed phenomena that enhance the plasma of the inner magnetosphere to high energies. They are defined by the characteristic trace in indices that measure the variation of the north-south component of the Earth’s magnetic field, such as the Dst or SYM-H. These indices are not purely measures of the symmetric ring current but include components of other current systems within the magnetosphere, primarily the tail and magnetopause currents. Using the methodology of Asikainen et al. [2010] the SMR index has been deconstructed to observe the evolution of the aforementioned current systems over the storm durations. Reeves et al. [2003] showed that only half of all storms caused an increase in the relativistic electron flux at geosynchronous orbit. For the remaining half the electron flux either does not change or decreases. It has been shown that the ring current decays faster for flux decrease storms than flux increase storms. Using a superposed epoch analysis, of geomagnetic indices and solar wind parameters, it has also been shown that although flux increase storms tend to have faster, less dense solar wind in the recovery phase of storms, it appears that it is the orientation of the IMF, which remains more southward in the recovery phase, that is the key parameter. This allows for the continued injection of plasma sheet particles into the inner magnetosphere. Further evidence to support this has been shown with the hydrogen and helium fluxes mirroring that of the electron flux. Finally, potential wave modes were evaluated over storm durations and potential acceleration mechanisms were noted as being more intense during flux increase storms than flux decrease storms; this is most likely due to the increase in the seed particles necessary for their generation.